2014
DOI: 10.1007/978-3-319-05936-5_1
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Prospects of Microbial Diversity in Rhizosphere

Abstract: Biodiversity is an appealing aspect including microorganisms encompasses diverse assemblage of organisms exhibiting with morphological, physiological, biochemical, metabolic and ecological diversity. At the level of taxonomic diversity microorganism signify phenotypic and genotypic diversity. Whereas, phenotypic diversity physiologically diversify the population of bacteria on the other hand, genotypic diversity explore the genetic divergence within the bacterial population. Functional diversity in the rhizosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 130 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…Actinobacteria have been shown to represent a large fraction of microbial populations in root systems31 and are well-known as inhabitants of saprophytic soil32. They have the ability to produce a rich source of important natural products, especially antibiotics that suppress the growth and development of a wide range of soil-dwelling plant pathogens1333435. Previous studies have shown that 140 to 160 antibiotics have been used in human therapy and agriculture, 100 to 120 of which were produced by Actinobacteria36.…”
Section: Discussionmentioning
confidence: 99%
“…Actinobacteria have been shown to represent a large fraction of microbial populations in root systems31 and are well-known as inhabitants of saprophytic soil32. They have the ability to produce a rich source of important natural products, especially antibiotics that suppress the growth and development of a wide range of soil-dwelling plant pathogens1333435. Previous studies have shown that 140 to 160 antibiotics have been used in human therapy and agriculture, 100 to 120 of which were produced by Actinobacteria36.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the proportion of variance ( R 2 ) attributable to combinations of these identified features ranged from 0.31 to 0.38, which was on the lower end of the variance explained by our multivariate Bayesian models containing multiple features (mean R 2 = 0.4; Table S3 at https://doi.org/10.6084/m9.figshare.c.5787851.v1 ). Although our decision to select features at the ASV level risks dispersing slightly different 16S rRNA gene sequences that may originate from the same genome into separate entities ( 47 ), this approach addresses strain-level heterogeneity that may provide insight into variability in rhizosphere functional potential ( 48 50 ). Connectivity patterns allow us to at least partially resolve this issue: despite sharing 99.2% sequence identity, two Flavobacterium ASVs (6 and 37) that negatively cooccur with each other and have different effects on plant growth ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The practice of maintaining mineral nutrients in soil and plant systems is known as nutrient management. This strategy derives from integrated nutrient management (INM), which concentrates on the nutrients nitrogen (N), phosphorus (P), and potassium (K) by combining agrochemicals with efficient microorganisms (EM) [3,4] . Endophytes have been utilized to expand the range of soil fertility and mineralization or immobilization of various trace elements, such as N, P, K, Zn, Fe, Cu, Mg, and S, according to the principles of mineral nutrient management (MiNuM).…”
Section: Introductionmentioning
confidence: 99%